Comparison on outcome for closed fracture radius and ulna in children treated with cast and intramedullary K-wire - Kamarul Izham, Kamarudin (2011)
This is a retrospective study which was conducted to compare between intramedullary kwire fixation and cast for the treatment of closed fracture midshaft of radius and ulna in children. Thirty one patients treated with cast and twenty patients treated with intramedullary kwire were traced from Hospital Sultanah Bahiyyah, Alor Setar from 2004 to 2009 between the age of 8 to 14 years old. • Cases were evaluated in 2 groups, one treated with cast and another group of patients treated with intramedullary k-wire. All patients were evaluated for radiological outcome at 1 week and 6 week, clinical outcome in terms of range of supination and pronation at 6 week follow-up by grading them using Daruwalla Grading and surgical complication of intramedullary k-wiring at 6 week. There was no significant difference between the two methods of treatment in their effectiveness to prevent angulation at fracture site at week 1 follow-up (mean: IM k-wire 7.75°; cast 6.39<l) with p value more than 0.05. The difference at week 6 follow-up also not significant (mean IM k-wire 7.85°; cast 7.03°) with p value more than 0.05. There was also no significant correlation between the two methods of treatment and the clinical outcome. Age was the most determinant factors on the clinical outcome based on Daruwalla grading system. However, gender and side hand dominant have no effect on clinical outcome. The treatment method have no effect on clinical outcome on Logistic Regression test. As a conclusion, there was no significant different between intramedullary k-wiring and cast in the management of closed fracture midshaft of radius and ulna in children in terms of preventing fracture angulation and restoring range of supination and pronation. This study also showed that age was the single most important factor to determine the clinical outcome of the patients with this type of fracture.